THE ROLE OF ACUTE-PHASE REACTANTS IN PATIENTS WITH RHEUMATOID ARTHRITIS - Spasovski, Dejan; Sandevska, Emilija; Balkanov, Svetlana Krstevska; Veljanovska, Aleksandra Pivkova (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Radiographic evaluation is still the most important tool for assessing structural damage to joints and the skeleton. The progression of the radiographic damage to the joints in the hands and feet is an important and objective variable for assessing the disease's activity as well as predicting the outcomes of treatment. In this study, radiographic assessment of the hand joints, acute phase reactants (ESR and CRP), and ACPA autoantibodies were used to assess the disease activity in RA patients treated with methotrexate therapy. Their roles as prognostic indicators of disease outcome were also examined. The serum of 70 participants (35 in the untreated RA group and 35 in the control group) was tested using the ELISA method DIA-STATTM Anti-CCP (Axis-Shield Diagnostics). In the same participants, RF was determined using the agglutination test (Latex RF test). Patients were treated with methotrexate at an average dose of 10 mg once weekly. For clinical evaluation of disease activity in every patient's radiographic index (RI), sedimentation, CRP, and RF were analyzed at certain time intervals (baseline, after 6, 9, and 12 months). The dynamic changes in the mean values of the RI score, sedimentation, CRP, and RF were used to assess RA. RI showed an increased radiographic progression of hand joint damage at time intervals between baseline and 9 months (p = 0.0167) and between baseline and 12 months (p = 0.0089). Statistical analysis showed statistically significant differences among the mean values of ESR in the four time intervals (p = 0.00002). Also, statistically significant differences were shown in the mean values of CRP in the four time intervals (p = 0.0488) (standard deviations showed great variations). At baseline, progression was seen in 3 (10%) patients, after 6 months in 13, and after 9 and 12 months RI progression was seen in 15. It was also observed that most patients had increased values of RF and CRP. Despite the methotrexate therapy, progression of the radiographic damage followed, especially in patients with increased values of sedimentation, CRP, and RF with persistence of previous hand joint erosions, as predictors of the aggressive course of disease. Keywords : Rheumatoid arthritis, Rheumatoid factor, Reactants of the acute phase.